Meta-Evaluation of IEG Evaluations (FY15-19) - Independent Evaluation Group (Washington, DC: World Bank, 2022)
IEG’s meta-evaluation serves as an input for the upcoming independent external review of its evaluations. The report focuses on aspects of credibility related to the rationale, focus, use of innovative methods, and various research design attributes as formulated in evaluation reports and their respective approach papers. Drawing on a set of 28 evaluations published from fiscal year 2015 to 2019, the meta-evaluation offers six major conclusions and suggestions based on a systematic review of evaluation scope, reliability, validity (including construct, internal, external, and data analysis validity), consistency, and the integration of innovative methods.